PENENTUAN PORTOFOLIO SAHAM YANG EFISIEN PADA LIMA PERUSAHAAN MINYAK DAN GAS BUMI (MIGAS) - Marwansyah, Sofyan (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2010)
Portfolio is a combination of assets owned by an investor both real assets and financial assets. In relation to stocks, the portfolio is a collection of stock from various companies owned by an individual investor. Portfolio consisting of various other types of stocks is not diversification is the result of investment made by investors. The advantage of a stock portfolio is a weighted average of the profits of each share is included therein. Investments made by investors during this only in non-oil sector, while most of the government budget is obtained from oil and gas sector. Currently the world's oil and gas business of special concern to both government and for investors. Investors and potential investors in determining the preferred shares are usually more accurate because it is important to know that investing in the stock market is not always beneficial and have a risk of failure experienced by the company's stock value. The purpose of forming portfolios is that can be verified by determining the selected stock with some proportion of the funds will be invested in each stock in order to achieve optimal results. The purpose of this paper is to determine an efficient portfolio of stocks at 5 (Five) Oil and Gas company. Securities analysis used in this paper is fundamental analysis. The data used are annual data on stock price growth and dividends paid from five oil and gas company registered as a company with the working system of PSC (Production Sharing Contract) at BPMIGAS years 2002-2006. Results showed that of five oil and gas company stock over five years, a portfolio combination of optimal portfolio is the portfolio 18, the portfolio with a gain of 0.62954 and 0.52181 at risk, ie a combination of 50% Total and 50% Premier Oil.